2014
DOI: 10.3390/rs70100256
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Slope as an Indicator of Pasture Quality

Abstract: Abstract:In this study, we develop a spectral method for assessment of pasture quality based only on the spectral information obtained with a small number of wavelengths. First, differences in spectral behavior were identified across the near infrared-shortwave infrared spectral range that were indicative of changes in chemical properties. Then, slopes across different spectral ranges were calculated and correlated with the changes in crude protein (CP), neutral detergent fiber (NDF) and metabolic energy conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…NDF CP (1) The conventional method for obtaining these indicators of pasture quality (CP and NDF) is based on in-situ sampling and chemical analysis. However, this conventional methodology involves intensive field work and lengthy laboratory analysis, which are relatively expensive and sometimes belated, making them unpractical for day-to-day farm management [5,6,10,14].…”
Section: Pqdi =mentioning
confidence: 99%
See 1 more Smart Citation
“…NDF CP (1) The conventional method for obtaining these indicators of pasture quality (CP and NDF) is based on in-situ sampling and chemical analysis. However, this conventional methodology involves intensive field work and lengthy laboratory analysis, which are relatively expensive and sometimes belated, making them unpractical for day-to-day farm management [5,6,10,14].…”
Section: Pqdi =mentioning
confidence: 99%
“…Pasture quality can be quantified by certain parameters, such as neutral detergent fiber (NDF) and crude protein (CP) content [10]. It is known that high CP content and low NDF content indicate higher quality pastures [11], which is usually the case when the plants are young.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study [28], we found that when using slopes across selected spectral ranges of dried and ground vegetation, it was possible to evaluate several pasture quality indicators with high accuracy, such as CP, NDF and metabolic energy concentration. However, that study was restricted to estimates based only on the spectra of dry samples; adjusting the method to fresh vegetation would enable further in-situ analyses, and this was the aim of the present study.…”
mentioning
confidence: 99%
“…Hence, calculating the absorbance area of the water bands (e.g., 1200, 1400, 1780, and 1940 nm) [11,43,44] can be a good indicator of water concentration in the vegetation. The spectral absorption features centered at 1940 nm have been found to be good indicators of plant water content [34,45,46]. Therefore, the area between the straight line and the absorption line ( Figure 2) was calculated (see [35] for more details).…”
Section: Calculating the Water-absorption Areamentioning
confidence: 99%
“…To develop a model to assess Cl and Na content in vegetation based on the slope method [34,35], we used the common CR spectral technique [9,[36][37][38][39][40]. CR normalizes reflectance spectra to a common baseline, enabling the identification of individual absorption features.…”
Section: Slope Calculation and Data Analysesmentioning
confidence: 99%